Restless legs syndrome and all-cause mortality in four prospective cohort studies - Szentkirályi, András (BMJ Group, 2012)
OBJECTIVES: To evaluate the association between restless legs syndrome (RLS) and all-cause mortality. DESIGN: Four prospective cohort studies. SETTING: The Dortmund Health Study (DHS) and the Study of Health in Pomerania (SHIP) from Germany. The Women's Health Study (WHS) and the Physicians’ Health Study (PHS) from the USA. PARTICIPANTS: In DHS: a random sample (n=1 299) from the population of Dortmund; in SHIP: a sample (n=4 291) from residents living in West Pomerania were drawn by multistage random sampling design; in WHS: female healthcare professionals (n=31 370); in PHS: male physicians (n=22 926) MAIN OUTCOME MEASURES: All-cause mortality. RESULTS: The prevalence of RLS ranged between 7.4% and 11.9% at baseline. During follow-up (ranging between 6 and 11 years) RLS was not associated with increased risk of all-cause mortality in any of the four cohorts. The multivariable-adjusted HRs (95% CI) for all-cause mortality ranged from 0.21 (0.03 to 1.53) to 1.07 (0.93 to 1.23) across the four studies. The HRs for all-cause mortality did not differ according to gender. CONCLUSIONS: In these four independently conducted large prospective cohort studies from Germany and the USA, RLS did not increase the risk of all-cause mortality. These findings do not support the hypothesis that RLS is a risk factor for mortality of any cause.